Work over welfare : the inside story of the 1996 welfare reform law - Haskins, Ron (Brookings Institution Press, 2006)
Work over Welfare tells the inside story of the legislation that ended ''welfare as we know it.'' As a key staffer on the House Ways and Means Committee, author Ron Haskins was one of the architects of the Personal Responsibility and Work Opportunity Act of 1996.